SENYAWA FENOLIK, ORYZANOL, DAN AKTIVITAS ANTIOKSIDAN BEKATUL YANG DIFERMENTASI DENGAN Rhizopus oryzae - Faizah Faizah; Feri Kusnandar; Siti Nurjanah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Rice bran is a by-product of milled rice. It contains bioactive compounds, such as total phenolic compounds and g-oryzanol known to have antioxidant activities. However, these bioactive compounds are chemically bound in the lignin matrix of the rice bran. Fermentation process potentially releases the bound forms of the active compounds to become the free ones. In this research, the rice brans of three varieties, i.e. Inpari 24 (red rice), inpari 30 (white rice), and koshihikari (white rice), were fermented using Rhizopus oryzae for 0, 24, 48, 72, 96 and 120 hours. Those showed highest antioxidant activities by DPPH assays were selected for further chemical composition analyses (moisture, ash, fat, protein, and carbohydrate), total phenolic compound, and g-oryzanol. The fermentation process significantly increased (P<0.05) the antioxidant activities of all rice brans and those fermented for 72 hours showed the highest antioxidant activities. This fermentation condition resulted in significant increase in moisture, ash and protein contents, while decreasing the fat and carbohydrate contents. The total phenolic compound and g-oryzanol of the three fermented rice brans increased significantly (P<0.05). The fermented rice bran of Inpari 24 variety showed the highest antioxidant activity, total phenolic compound, and g-oryzanol contents as compared to those of Inpari 30 and Koshihikari varieties.